Analysis of Underpassing Skills in Volleyball Game for Students Interested in Sports Talent in Sports Education Muhammadiyah University of Surakarta - Syabilul Yusup Bachtiar Khamal; Vera Septi Sistiasih (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The purpose of this study was to look at the Underpassing Skills in Volleyball Games for Students who are Interested in Sports Talent in Sports Education at the Muhammadiyah University of Surakarta. The sample in this study was  Volleyball athletes interested in sports education talent with a total sample of 33 while for sampling techniques using purposive sampling. Data collection techniques using observation while this type of research is descriptive research using a quantitative research type approach. Based on the results of the study obtained, it can be concluded that the passing skills of men in MBO Sports Education students, from a total of 18 people in the sample studied, 10 sample people were in the interval of >47 with a score of 55.56%, 5 sample people were in an interval of 40-46 or with a score of 27.78%, 2 sample people were in an interval of 27-39 with a score of 11.11%,  1 sample person was in an interval of 17-26 with a value gain of 5.56%, and 0 sample people were in an interval of <16.